Kajian Penanda Genetik Tarsius bancanus dan Tarsius spectrum dengan Sekuen D-Loop Parsial DNA Mitokondria - Widayanti, Rini; Solihin, Dedi Duryadi (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
The objective of this research was to study the specific genetic marker on D-loop region of Tarsius bancanus and Tarsius spectrum. The sequencing of PCR product using primer DLTARPROF on D-loop resulted in base sequence of 270 nts. Result of D-loop fragments sequencing was put on multiple alignment with other primates from Genbank with the aid of software Genetyc-Win Version 3.0 and Clustal W, and was analyzed using MEGA program version 3.1. The genetic distance was based on nucleotide D-loop, the smallest genetic distance was 0% and the biggest was 11.8% and the average was 2.3%. The phylogenetic tree using neighbor Joining Method based on some nucleotide sequence on D-loop region could not be used to differentiate between Tarsius bancanus and Tarsius spectrum.